Noisy condition and three-point shot performance in skilled basketball players: the limited effect of self-talk - Yang, Liu; Tian, Yu; Wang, Yingchun (Frontiers in Sports and Active Living, 2024)
In modern basketball, the three-point shot plays an important tactical role. Basketball players often face the distraction from audience and opponents, necessitating psychological skill to maintain their performance. The study examined the effects of self-talk interventions on the three-point shot performance under quiet and noisy conditions. It involved 42 national second-level basketball players and used a 2 (Condition: quiet condition, noisy condition) × 3 (Intervention: control group, motivational self-talk, instructional self-talk) mixed design to investigate the performance of the static and dynamic three-point shots tasks. The results revealed that the static three-point shot score was significantly lower in noisy condition compared to quiet condition (p = 0.016), while the main effect of Intervention and the interaction effect of Condition × Intervention were not significant. Post-hoc analysis indicated that only the control group showed significantly lower scores in the noisy condition (p = 0.043). For the dynamic three-point shots performance, there were no significant main effects of Intervention or Condition, nor any significant interaction effect between Condition and Intervention. In conclusion, noise distraction negatively affects the static three-point shots task, and although self-talk interventions can mitigate such negative effects, their effectiveness is limited for dynamic three-point shots task with high physical demands.